ME+YOU=MET: ACTIVATION OF THE COFFEE SHOP PUBLIC SPACE INTO A THEATER PERFORMING ARTS SPACE WITH AN ENVIRONMENTAL THEATER AND POST DRAMATIC APPROACH - Wahyuni, Yeni; Yusril, Yusril (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This research examines the transformation of a public coffee shop space into a theater performing arts space by applying environmental theater and post-dramatic theater approaches. Public spaces, especially coffee shops, have great potential as alternative spaces for theatrical performances, given their informal characteristics and ability to attract various levels of society. The environmental theater approach emphasizes interaction between audience and actors as well as non-conventional use of space, thereby blurring the boundaries between stage space and audience space. Meanwhile, post-dramatic theater, which emerged as a response to traditional theater structures, prioritizes elements such as visuals, sound, and movement over linear narrative. The performance Aku+Kamu=Bertemu moves the perspective form of the arena stage and proscenium to the public space, by reading the issues in the public space. The conclusion from the Aku+Kamu=Bertemu performance is that integrating public spaces such as coffee shops into theater performing arts practices can revive the local culture and create a space for dynamic social interaction. This study also offers practical guidance for theater practitioners and coffee shop owners in designing and executing performances that take full advantage of the potential of these public spaces. Thus, this thesis contributes to the development of new strategies in the performing arts and public space management.